Transport resilience: The Occupy Central Movement in Hong Kong from another perspective. (December 2017) - Loo, Becky P.Y.; Leung, Kevin Y.K.
Highlights: Hong Kong's Occupy Central (OCM) is studied from a transport resilience angle. OCM had three phases from chaos to a new equilibrium. Transport ridership and vehicle flow data before, during and after OCM are analysed. Joint effort of government, industry and public are crucial for transport resilience. Abstract: This paper looks at the Occupy Central Movement (OCM) in Hong Kong from an innovative and understudied angle of transport resilience. With the OCM as a shock event, subsequent responses may be conceptualised as having three different phases. Phases One and Two refer to chaos at an adverse event's initial outbreak, and the subsequent state of flux. Phase Three may or may not exist; it sets in when people in the society accept these adaptations as longer-term arrangements. Fragmented data and information about the severe disruptions and ensuing changes of the transport system during and after this shock event have been carefully assembled and systematically analysed in relation to the actions and adaptations made by the Government, the industry and the general public. With increasing urbanisation, all stakeholders, including city governments, the industry and the general public, need to be more prepared for large-scale disruptions caused not just by natural hazards but also human beings. Government actions alone are not sufficient. Speedy and concerted responses of the industry are indispensable in achieving transport resilience. Effective dissemination of information through different channels is critical. Moreover, there needs to be concrete steps towards establishing Key Resilience Performance Indicators for cities, covering both the hardware and software components of a transport system.